Towards strategies for making offshore outsourcing economically and socially sustainable. (1st April 2008) - Monique Ramioul,; Tom De Bruyn,
Abstract : This paper looks at the role trade unions and employee representatives can play in workplaces where offshoring and outsourcing projects are introduced. Starting with an overview of the literature on the employment impacts of offshore outsourcing, it highlights a strong contrast between the generally optimistic macro-economic studies focusing on the net effects, and the realities of offshore projects revealed through case studies, in which failure and mismanagement are common. It describes a situation in which increasing numbers of European trade unions, acknowledging that offshore outsourcing is 'here to stay', have reacted to this situation by developing a more pro-active approach to the introduction of outsourcing and offshoring which seeks to avoid the negative impacts on employees of failed or badly managed offshore outsourcing projects. Finally, the paper discusses the MOOS (Making Offshore Outsourcing Sustainable) project which exemplified this approach, aiming at contributing to a better informed and more effective role for employee representatives, to enable them to assess and influence the offshore outsourcing practices of their employers.